Fluidized Bed Roasting Of Micro-Pelletized Zinc Concentrate: Part II?Particle Entrainment And Residence Time ? Synopsis - S. Heukelman (The Southern African Institute of Mining and Metallurgy, 2011)
Zincor uses O2 enrichment (up to 26% O2 in the fluidizing air) to increase the processing rate of zinc concentrates in the fluidized bed roasters. The aim of this study is to determine whether O2 enrichment can be reduced by introducing micro-pelletized concentrate into the feed blend, while maintaining current roaster feed rates and calcine quality. It was found that, with a load of 20% micro-pellets introduced into the feed blend, that O2 enrichment could be reduced by 60%. It was determined that entrained particles spend on average between 0.46 hour and 2.44 hour in the roaster, compared to particles remaining between 3.93 hour and 4.00 hour in the bed overflow. This compares well with a radioactive tracer test performed by Spira. The required reaction time for micro-pellets was found to be less than the residence time inside a Zincor roaster. The result achieved indicated that the average particle residence time inside the roaster was increased successfully in order to compensate for the longer reaction time required to roast micro-pellets at lower levels of O2 in the fluidizing air.